New Plants for Florida: Tropical Pumpkin - Richard L. Jones; Mary Duryea; Berry J. Treat (EDIS)
Tropical pumpkin (Cucurbita moschata Duchesne), also known as calabaza, calabash, auyama, ayote, or zapallo, is a species of pumpkin that is grown throughout the tropics and subtropics. Tropical pumpkins are a valuable source of dietary carotenoids that have a major role in nutrition as provitamin A and antioxidants. Carotenoid concentrations in tropical pumpkin compare favorably with those in butternut squash. This document is part of Circular 1440, a publication of the Florida Agricultural Experiment Station, the Agronomy Department and IFAS Communication Services, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date August 2003. Originally published as a booklet by IFAS Communication Services June 2003.